The Application of the Philosophy of Sufficiency Economy for Development by People in Nongsarai Sub-district, Phanomthuan District, Kanchanaburi Province - Cumnongkul, Netrchanok; Mahaacha, Wanippol; Sirihiran, Sombun; Amarasiripong, Somsak (Academic MCU Buriram Journal, 2016)
The objectives of this research were to study the practice of the principle of sufficiency economy and to suggest means for the development of the practice in Nongsarai sub-district in Phanomthuan district. A quantitative data was gathered by from the paticpats residing in the area survey using questionnaires. The demographic data, revealed that most subjecth were female with the age of 41-50 years old and possess of elementary education. They were agriculturalists with an average monthly income of 10,001-15,000 Baht. The sample had population put the principle into practice both in their daily life and working, in the aspects of moderation, reasonableness, risk management along with the conditions of knowledge and virtue at the level of ‘the most’. When considering the individual factors in the practice of the principle, the differences of gender, age, and educational level significant affected the practice of the concept at a statistical level of 0.05.